2009
DOI: 10.5005/jcdp-10-2-67
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multiple Consecutive Applications of One-step Self-etch Adhesive on Microtensile Bond Strength

Abstract: Aim:The aim of this study was to evaluate the effects of multiple consecutive coatings of a one-step self-etch adhesive system (Clearfil Tri-S Bond) on the microtensile bond strength (MBS) to dentin. Methods and Materials:Nine caries-free human lower third molars were sectioned perpendicular to the long axis to expose the mid-coronal dentin. The teeth were separated into three experimental groups (n=3) according to the number of adhesive resin coats applied. In Group 1 one layer of Clearfil Tri-S Bond was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…Nevertheless, bond strength should not be associated only to the formation of resin tags, but also to the penetration of resin monomers into intertubular dentin. 6 Results of the present study are different from those of Arisu et al 16 which found that the application of three consecutive layers significantly increased bond strength of an one-step adhesive (Clearfil Tri S Bond, pH 2.7). 21 Clearfil Tri S Bond adhesive has a lower pH (more acidic) than Adper Easy One adhesive (which has a pH of about 3.5).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, bond strength should not be associated only to the formation of resin tags, but also to the penetration of resin monomers into intertubular dentin. 6 Results of the present study are different from those of Arisu et al 16 which found that the application of three consecutive layers significantly increased bond strength of an one-step adhesive (Clearfil Tri S Bond, pH 2.7). 21 Clearfil Tri S Bond adhesive has a lower pH (more acidic) than Adper Easy One adhesive (which has a pH of about 3.5).…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly, adhesive monomer penetration may be deeper with the application of a 2.7 pH adhesive (Clearfil Tri S Bond) as opposed to a 3.5 pH adhesive, such as that used in this study. This may explain the increase in bond strength to sound dentin reported by Arisu et al 16 Similarly, Bellis et al 17 found that the additional coats of ultramild pH adhesives (Clearfil Tri S Bond, pH 2.7 and Adper Easy Bond, pH 2.5) helped improve microtensile bond strength to sound dentin.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These findings might raise concerns considering that applying two or more layers has previously been suggested for one‐step self‐etching systems to increase bond strength . However, Taschner et al (2014) showed that the effect of additional layers on bond strength is dependent on material and that this procedure did not improve the performance of SBU.…”
Section: Discussionmentioning
confidence: 99%
“…These findings might raise concerns considering that applying two or more layers has previously been suggested for one-step self-etching systems to increase bond strength. [20][21][22] However, Taschner et al (2014) 23 showed that the effect of additional layers on bond strength is dependent on material and that this procedure did not improve the performance of SBU. Therefore, it can be considered that thicker layers of this adhesive are not recommended because it increases the risk of misinterpretation in radiographic images, leading to incorrect indication of restoration replacement.…”
Section: Discussionmentioning
confidence: 99%